Making a Profile of Karanggunung Hamlet for Community Empowerment in Gunung Kidul Regency - Ikram, Nur Muhammad; Gupitasari, Nihan Ayu Shabrina; Prawira, Hadi (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
Currently, the Government of the Republic of Indonesia has issued a policy so that stakeholders in each village can have full authority in regulating and managing community needs and can be on target. To support this, we need programs that can support the achievement of these policies. Therefore, a profile video was made for Karanggunung Hamlet. The purpose of holding this program is to help Karanggunung Hamlet in disseminating general information along with the potential of Karanggunung Hamlet more broadly. The method used in this community service activity is by conducting interviews with community leaders followed by recording a video about the profile of Karanggunung hamlet. Next, video editing is carried out to produce a profile video about Karanggunung Hamlet. The result of this activity is a video profile of Karanggunung hamlet which has been uploaded via YouTube social media as a form of branding for Karanggunung hamlet.